RECONSTRUCTION OF GROUP AND PHASE VELOCITY OF LOVE WAVE AND SHEAR VELOCITY IMAGING IN NUSA TENGGARA ISLANDS USING AMBIENT NOISE TOMOGRAPHY - Nugroho, Nursyamhadi
The Nusa Tenggara islands is an area characterized by subduction of the Indo-Australian plate under the Eurasian plate in the southern part and there is push from a back arc in the northern part so that it is a tectonically active area. This research was conducted using the ambient noise tomography (ANT) method which utilizes seismic noise records recorded by 30 seismometers of BMKG network with a recording time span of one year (January - December 2016). The data used is the Love waves, which is obtained from the transverse component. The cross-correlation process between station pairs is carried out to obtain the Green’s function. The period range of the obtained dispersion curves is in the range of 8 - 38 s with the direction of the noise source location generally south-southeast relative to the seismic network. Dispersion curve is determined using the Frequency Time Analysis (FTAN) method. The set of dispersion curves is then used as an input to make the group and phase velocity maps over the related period range. Then, the set of dispersion curves obtained from the tomography of the group and phase velocities are inverted using the RR-PSO algorithm to obtain the shear velocity model. Based on the shear velocity structure, it is found that the northern part of the Nusa Tenggara Islands is dominated by low velocity anomalies which may be due to magma fluid because the area is a volcanic arc. High anomaly down to a depth of ~7 km on the island of Timor is indicated as a lift of the crust due to the collision process.